2013
DOI: 10.1371/journal.pone.0061177
|View full text |Cite
|
Sign up to set email alerts
|

Design and Initial Results of a Multi-Phase Randomized Trial of Ceftriaxone in Amyotrophic Lateral Sclerosis

Abstract: ObjectivesCeftriaxone increases expression of the astrocytic glutamate transporter, EAAT2, which might protect from glutamate-mediated excitotoxicity. A trial using a novel three stage nonstop design, incorporating Phases I-III, tested ceftriaxone in ALS. Stage 1 determined the cerebrospinal fluid pharmacokinetics of ceftriaxone in subjects with ALS. Stage 2 evaluated safety and tolerability for 20-weeks. Analysis of the pharmacokinetics, tolerability, and safety was used to determine the ceftriaxone dosage fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 30 publications
1
78
0
2
Order By: Relevance
“…These studies showed that ceftriaxone decreased glutamate-mediated excitetoxicity and reduced SOD (superoxide dismutase) induced neurotoxicity [8]. Ceftriaxone also underwent trials for the possible treatment of ALS (amyotrophic lateral sclerosis) [9][10][11][12]. Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder caused by loss of cortical, brainstem and spinal motor neurons [9].…”
Section: Methodsmentioning
confidence: 99%
“…These studies showed that ceftriaxone decreased glutamate-mediated excitetoxicity and reduced SOD (superoxide dismutase) induced neurotoxicity [8]. Ceftriaxone also underwent trials for the possible treatment of ALS (amyotrophic lateral sclerosis) [9][10][11][12]. Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disorder caused by loss of cortical, brainstem and spinal motor neurons [9].…”
Section: Methodsmentioning
confidence: 99%
“…В рандомизированном двойном слепом плацебо-контролируемом ис-следовании безопасности применения цефтри-аксона для лечения латерального амиотрофи-ческого склероза показано, что использование препарата в низких (2 г/сут) и высоких (4 г/сут) дозах в течение 20 недель сопровождается раз-витием псевдолитиаза приблизительно у 70 % пациентов без существенных различий между группами, но количество симптомных форм хо-лелитиаза больше среди пациентов, получавших высокие дозы антибиотика [7].…”
Section: íà äîïîìîãó ïåä³àòðóunclassified
“…продемонстрировали, что урсодезоксихолевая кислота позволяет сократить длительность и ускорить разрешение цефтриаксон-индуцированного псевдолитиаза, что дает основа-ния рекомендовать включение урсодезоксихолевой кислоты в качестве сопровождения антибактери-альной терапии для профилактики развития холе-литиаза [7]. Пролонгированное исследование эф-фективности использования урсодезоксихолевой кислоты в дозе 300 мг/сутки подтвердило достовер-ность снижения частоты гепатобилиарных побоч-ных эффектов [13].…”
Section: лечениеunclassified
“…Recent findings have shown that antibiotics of the -Lactam family increase the expression of EAAT2 and lead to delayed disease progression and increased survival in mouse models [53]. Unfortunately, the clinical trial of these antibiotics in ALS patients was stopped at Phase III due to inability to reach the specified efficacy criteria [54]. Although a disappointing result, hope remains that increasing glutamate transporter expression within astrocytes may be a potential treatment option.…”
Section: Potential Therapeutic Strategiesmentioning
confidence: 99%